KEPEMIMPINAN TRANSFORMASIONAL, PERILAKU WIRAUSAHA PENGURUS DAN PENGARUHNYA TERHADAP PARTISIPASI ANGGOTA SERTA IMPLIKASINYA TERHADAP KINERJA KOPERASI DI PROVINSI GORONTALO - Abd. Rahman Pakaya (Indonesian Journal of Economics and Business, 2012)
The aims this study is obtaining empirical evidence and find clarity about the phenomenon of the influence of Transformational Leadership, Entrepreneurial Behaviour of Management on members participation and the impact to the performance of this Cooperative in the Province of Gorontalo. This study refers to a structured framework in the form of hypotheses to determine the effect of transformational leadership, entrepreneurial behavior on the participation of members of the board and its implications for the performance of cooperatives in the province of Gorontalo both simuktan or partial. The method used in this research is verification methods and the research form is a descriptive - reseach. Structural Equation Modeling (SEM) analysis tool is used to test the hypothesis. The results of hypothesis testing indicate that the transformational leadership, entrepreneurial behavior simultaneous and the partial effect on the participation of members. Transformational leadership, entrepreneurial behavior affects directly or indirectly (through participation) on the performance of cooperatives.  Member participation  influence on the performance of cooperatives in the province of Gorontalo.  The implications of these findings for practitioners and researchers are expected to about contribute to the implementation of the three variables mentioned above mainly in increasing the participation of members in order to there are the board of cooperative performance in the province of Gorontalo.